New artery clamping technique with mononylon 5.0. in microsurgery. Experimental study in rats - Huaraca, Walter Francisco (Revista Universidad de Guayaquil, 2010)
Microsurgery is a very common and important technique in plastic surgery. Enables the implementation of free flaps and replantation. Clamping is essential because it stops the blood flow without damaging the vessel. This instrument is delicate, difficult and expensive to manufacture. Trying to find an useful alternative, Authors developed a wire nylon 5.0. clamp made. Background: Evaluating a new small caliper artery clamping method with mononylon 5.0. Method: 20 male wistar rats, weighing 220 to 250 g. were operated on by femoral artery anasthomosis using mononylon 5.0. clamping. Patency assessment was made by the milking maneuver after surgery and 72 hours. Results: Patency was registered 30 minutes after surgery in all cases. Only 4 animals showed patency after 72 hours and the remaining 16 developed artery thrombosis. Conclusions: This study proved that artery anasthomosis of small arms using wire mononylon 5.0. clamping, could be possible using described technique. (Huaraca Technique)